2014
DOI: 10.1111/apt.12691
|View full text |Cite
|
Sign up to set email alerts
|

The use of pharmacological prophylaxis against venous thromboembolism in hospitalised patients with severe active ulcerative colitis

Abstract: SUMMARY Background Hospitalised patients with inflammatory bowel disease are 1.5- to 3.5-fold more likely to develop venous thromboembolism compared to controls. Clinical guidelines recommend pharmacological prophylaxis. Aim To determine the rate of pharmacological venous thromboembolism prophylaxis prescription and administration in a cohort of hospitalised patients with severe active ulcerative colitis and to assess predictors of failure to order pharmacological prophylaxis at 24 h. Methods This is a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It is recognised that prophylaxis is justified by the size of thromboembolic risk among hospitalised inflammatory bowel disease patients, which leads to widespread acceptance that this should be routine. [5][6][7][8] We demonstrated that the risk of venous thromboembolism is also increased in ambulant inflammatory bowel disease patients, and the risk is higher in periods of bowel inflammation. 9 Our work did not demonstrate any additional period in which prophylaxis may be justified.…”
Section: Introductionmentioning
confidence: 78%
“…It is recognised that prophylaxis is justified by the size of thromboembolic risk among hospitalised inflammatory bowel disease patients, which leads to widespread acceptance that this should be routine. [5][6][7][8] We demonstrated that the risk of venous thromboembolism is also increased in ambulant inflammatory bowel disease patients, and the risk is higher in periods of bowel inflammation. 9 Our work did not demonstrate any additional period in which prophylaxis may be justified.…”
Section: Introductionmentioning
confidence: 78%
“…However, in selected patients with additional risk factors, the benefit may possibly outweigh the riskfor instance, ambulant IBD patients with active disease who have had a previous VTE, or who have cancer. We further think that according to guidelines, hospitalized patients who in general is sicker, should have anticoagulation [14]. The role of such complex risk stratification schemes could possibly be elucidated in further research.…”
Section: Discussionmentioning
confidence: 95%
“…However, a critical issue regarding pharmacologic thromboprophylaxis in IBD is its low rate of implementation in hospitalized patients despite guideline recommendations. Recently, three North American retrospective studies reported an overall pharmacological prophylaxis rate of 37–80% on admission …”
Section: Discussionmentioning
confidence: 99%